The Development of Enteral Formula “KAMEKAMA” Based on Red Beans (Phaseolus vulgaris L.) and Cinnamon (Cinnamomum verum) for Diabetes Mellitus - Maria Gracia Putu Novita Puryani; Yohanes Kristianto; Dwipajati Dwipajati (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Introduction: Treatment of diabetes mellitus in critical conditions using NGT can be done through the administration of enteral formulas, one of which is the KAMEKAMA enteral formula which has been developed with various modifications. Red bean flour and cinnamon flour as functional local foods can be developed into KAMEKAMA formula for diabetes mellitus. Objective: This study aims to develop an enteral KAMEKAMA formula based on red bean flour and cinnamon flour for diabetes mellitus using NGT. Materials and Methods: This type of research is experimental with a trial and error design. The final product is assessed based on organoleptic quality, viscosity and osmolarity, NGT hose flowability, color difference ratio (CDR), the selected development formula is carried out through an empirical test of the approach to energy and nutritional value according to RS standards. Organoleptic quality assessment with 20 moderately trained panelists and 10 trained panelists. Results: The best enteral formula according to the panelists was F4, which is the ratio of red beans to cinnamon (75:60), the content of the KAMEKAMA enteral formula is energy which is 1010.46 kcal, nutritional value of protein 37.29 grams, fat 39.10 grams, carbohydrates 145.32 grams, and fiber 34.77 grams. Viscosity 8 mPa's and Osmolarity 304 mOsm/L. Organoleptic quality in color, aroma, and texture did not have significant differences, but in taste and after taste there were significant differences. Conclusion: The utilization of red bean flour and cinnamon flour as functional local foods can be concluded as an alternative to the enteral formula of KAMEKAMA based on red beans and cinnamon for diabetes mellitus. Further research can carry out formula interventions in patients with diabetes mellitus and as well as formula glycemic index.